KETERAMPILAN BERBAHASA BAKU DALAM PRESENTASI ILMIAH MAHASISWA PROGRAM STUDI PENDIDIKAN BAHASA DAN SASTRA INDONESIA UNIVERSITAS NEGERI MAKASSAR - Salsabila; Muhammad Saleh; Nurhusna (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe students’ standard language skills in terms of phoneme pronunciation, word usage, and sentence construction in scientific presentations of students from the Indonesian Language and Literature Education Study Program at Universitas Negeri Makassar. This research employed a descriptive qualitative approach. Data were collected through observation, note-taking, and recording of students’ utterances during scientific presentation activities. Data analysis was conducted through transcription, data reduction, data display, and conclusion drawing. The results indicate that students’ standard language skills in scientific presentations are generally at a fairly good level, although several inaccuracies are still found. In phoneme pronunciation, errors such as omission, addition, and substitution of phonemes occur due to regional dialect influence. In word usage, students still use foreign loanwords that are not in accordance with standard Indonesian equivalents. In sentence construction, incomplete sentences and inaccuracies in the use of subjects and predicates are identified. Therefore, consistent practice in using standard Indonesian in academic contexts is necessary.